A novel damping based feature for rich resin defect detection in a four layer composite plate using S0 Lamb mode. Issue 6 (2nd November 2021) - Shafiei Alavijeh, Maryam; Soorgee, Mohammad Hossein
ABSTRACT: In this paper, local damping behaviour of S0 ultrasonic Lamb mode is investigated to determine the reason of amplitude reduction of signals come from a rich resin defect in a composite plate. A four-layer woven glass fibre-epoxy (WGF/epoxy) composite plate, containing a predefined rich resin area as the damage, has been manufactured and inspected with S0 Lamb mode via through transmission and pulse-echo method. Results have shown that there is a considerable amplitude reduction in the transmitted wave while a negligible damage reflected wave has been captured in the related receiver. An experimental based method has been employed in order to extract Rayleigh damping coefficients for the healthy composite plate, followed by a novel methodology to evaluate the damping coefficients at the defected area. Having calculated Rayleigh damping coefficients for both damaged and undamaged areas of the composite plate, several finite element simulations have been carried out, in order to quantify the wave amplitude reduction due to attenuation at the damage. The Amplitude Reduction Ratio (%ARR), obtained from numerical simulation matches closely with experimental ARR, represents that the proposed method for Rayleigh damping coefficients evaluation at the rich resin area can be used for further rich resin defect investigations.